Survival of Bifidobacterium pseudocatenulatum G4 during the storage of fermented peanut milk (PM) and skim milk (SM) products - Kabeir, Barka Mohammed; Abd Manap, Mohd Yazid; Abdullah, Muhammad Nazrul Hakim; Khahatan, Ali; Shaborin, Anis; Mustafa, Shuhaimi (Academic Journals, 2009)
Survivability of Bifidobacterium pseudocatenulatum G4 in fermented peanut milk (PM) and skim milk(SM) directly or supplemented with fructooligosacharide (FOS) and human grade yeast extract was evaluated under refrigeration and 25°C for a period of 2 weeks. During the study period, the development of lactic acid and short chain fatty acids (acetic, propionic and butyric) were also examined. The fermented products were prepared utilizing inoculum of 0.67% and anaerobic incubation under control conditions using 1l volume bioreactor to final pH less than 5. Initial mean viable number of strain G4 ranged between 7.12 - 8.35 cfu/ml fermented PM and 7.28 - 8.39 cfu/ml fermented SM based products. The viable strain G4 in fermented samples held at 25°C for 2 weeks decreased to a level of < 7 log cfu/ml due to the pH reductions, which were explained by increases in lactic, acetic, propionic and butyric acids. This final viability of the fermented products is below the requirement to claim probiotic effects upon their consumptions, while at refrigeration (4°C) storage, the viability maintained in fermented products was higher exceeding the mean recommended level of 7 log cfu viable probiotic per ml product generally. Therefore, fermented PM products especially supplemented with FOS containing strain G4 could maintain probiotics effects under refrigeration for a period of 2 weeks.